Investigation of the basics and nature of obsessive-compulsive disorders and generalized anxiety - FatemehKaramiKalahroudi,; Liyaghat, Rita (International Journal of Psychosocial Rehabilitation, 2021)
Anxiety disorders cover a series of disorders and anxiety is one sign of them. The common aspect of the disorders is psychological suffering and anxious disorder appeared purely or in combination with other symptoms. Therefore, regarding the different positions of the experts in this field and based on a common point of the disorders, it could be accepted that any disorder with anxiety as the main symptom, whether the anxiety is appeared acutely or ambiguously, whether chronic or periodic can be in the domain of anxiety disorders. This study aims at presenting the nature and the basics of obsessive-compulsive disorders (OCD) and generalized anxiety.